Analisis Kondisi Spherical Roller Bearing terhadap Efisiensi Kinerja Mill Fan - Revaldo Nur Hidayat (CV. IRA PUBLISHING, 2025)
This study analyzes the condition of the spherical roller bearings of the Mill Fan at a cement plant in the Finishing Mill Unit. Spherical roller bearings are important components that affect the smoothness and efficiency of Mill Fan operation. The objective of this study is to analyze the relationship between the condition of spherical roller bearings and Mill Fan efficiency, calculate their theoretical life, and compare it with their actual field service life. The method employed involves collecting operational data from the central control room, such as pressure, shaft rotation, flow capacity, and motor power, and then calculating the efficiency and estimating the service life of the spherical roller bearings. The results show that the theoretical service life of the spherical roller bearings is 16.3 years, while the actual service life is only 8.5 years, or 51.5% of the design life. The Mill Fan efficiency before spherical roller bearing replacement was 68.92%; it decreased after replacement and then increased to 76.95% in the subsequent period. The conclusion of this study is that the difference between the theoretical and actual service life of spherical roller bearings is affected by lubrication quality, operating load, operating temperature, and cement dust contamination. Periodic condition monitoring and preventive maintenance are necessary to improve reliability and extend the service life of spherical roller bearings. This research provides a basis for evaluating more effective maintenance strategies and operational efficiency of Mill Fans in the cement industry.